2003
DOI: 10.1080/713840325
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of Low Molecular Weight Heparin into Polymeric Particles Designed with Biodegradable and Nonbiodegradable Polycationic Polymers

Abstract: Owing to its lack of oral absorption, heparin has to be administered parenterally. However, parental administration has negative aspects such as multiple injections, possible infection, patient inconvenience, and high cost. Now, low molecular weight heparin (LMWH) is taking part in antithrombotic treatment and is proven to confer more advantages than unfractionated heparin. The aim of our present study was to formulate, by the w/o/w emulsification process, LMWH microparticles as potential oral carriers prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 21 publications
2
33
0
5
Order By: Relevance
“…Although insulin (pI 5.4) is mainly negatively charged in the aqueous solution of PVA 0.1% (w/v) (pH 6.5), we can observe that the addition of insulin in the formulation did not affect the zeta potential of the nanoparticles, thus proving that insulin was effectively encapsulated into the nanoparticles. Indeed, some authors have demonstrated that encapsulation of heparin (which is negatively charged) decreased the zeta potential of microparticles (Jiao et al, 2002a;Hoffart et al, 2003); heparin was mainly adsorbed on the surface of the particles, involving a decrease of the zeta potential of unloaded particles (from +40 mV to −30 mV). In the case of nanoparticles prepared with Eudragit  RS alone or in combination of PCL, the lack of zeta potential difference between unloaded and loaded nanoparticles is in favor of the insulin encapsulation in the nanoparticles matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Although insulin (pI 5.4) is mainly negatively charged in the aqueous solution of PVA 0.1% (w/v) (pH 6.5), we can observe that the addition of insulin in the formulation did not affect the zeta potential of the nanoparticles, thus proving that insulin was effectively encapsulated into the nanoparticles. Indeed, some authors have demonstrated that encapsulation of heparin (which is negatively charged) decreased the zeta potential of microparticles (Jiao et al, 2002a;Hoffart et al, 2003); heparin was mainly adsorbed on the surface of the particles, involving a decrease of the zeta potential of unloaded particles (from +40 mV to −30 mV). In the case of nanoparticles prepared with Eudragit  RS alone or in combination of PCL, the lack of zeta potential difference between unloaded and loaded nanoparticles is in favor of the insulin encapsulation in the nanoparticles matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Outras formas encontradas para a análise quantitativa da HF são os métodos nefelométrico, descrito por Ardry, 14 e turbidimétrico utilizado em trabalhos mais recentes. [15][16][17] A turbidimetria é uma técnica relacionada à colorimetria, capaz de medir a turbidez de uma amostra, e possui aplicação restrita à quantificação de substâncias que podem ser precipitadas, utilizando reagentes apropriados, em condições que assegurem a formação de uma suspensão suficientemente estável para se obter reprodutibilidade. 18 Análises turbidimétricas têm sido utilizadas como alternativa para o doseamento de fármacos em diversas formas farmacêuticas.…”
Section: -4unclassified
“…Heparins' structure and stability has been the central core of many studies to find suitable drug delivery systems for their administration (Scala-Bertola et al, 2009). The drug load and release profiles obtained from studies on poly-lactic-co-glycolic acid polymer (PLGA)-based microspheres and nanoparticles (NPs) were not encouraging (Kreitz et al, 1997;Jiao et al, 2001;Hoffart et al, 2003Hoffart et al, , 2006 motivating other researchers to prepare microspheres with more satisfactory results (Rawat et al, 2008).…”
Section: Introductionmentioning
confidence: 99%